Beef cattle mineral nutrition in the brazilian pantanal. I. Macronutrients survey in central Nhecolêndia - Pott, Edison Beno; Brum, Paulo A. R. de; Almeida, Irajá L. de; Comastri Filho, José A.; Dynia, José Flávio (Pesquisa Agropecuaria Brasileira, 2014)
Results of analysis of soil, water and native forage sampled in three seasons, and blood and bone samples collected in four seasons, at central Nhecolandia's sub-region of the Pantanal Mato-grossense, Brazil, are presented. Soil and forages were sampled on five landscape units: forest, woodland, Elyonurus grassland, open grassland and ponds. In the soil, pH varied from 4.1 to 6.2; average levels of exchangeable cations and available P varied as follows; Al, from 6 ppm to 39 ppm; Na, from 1 ppm to 20 ppm; Ca, from 7 ppm to 350 ppm; Mg, from 2 ppm to 57 ppm; P, from 1 ppm to 16 ppm; K, from 16 ppm to 74 ppm. The highest levels of pH, Ca, Mg, P and K occurred in forest soil. In water, only Na and K of "salina" (brackish water pond) reached nutritional importance, averaging 319 ppm and 290 ppm, respectively. In forages, Ca varied from 0.11% to 0.33%; Mg, from 0.09% to 0.21%; K, from 0.72% to 2.74%; and P, from 0.09% to 0.31%. In the blood serum (mg/100 ml), Ca varied from 7.3 to 11.2; Mg, from 1.9 to 3.3; and P, from 3.6 to 6.0. In the bone, Ca, Mg and P concentrations, in November, were 31.2%, 0.41% and 11.9%, respectively; ash content varied from 57.6% to63.6%. These results suggest the possibility of occurrence of Ca, Mg and P deficiencies in the diet of cattle grazing in this area, during certain seasons.